1984
DOI: 10.1007/bf00000465
|View full text |Cite
|
Sign up to set email alerts
|

The composition, nutritional status and digestibility of the diets of Sarotherodon mossambicus from nine man-made lakes in Sri Lanka

Abstract: SynopsisThe dietary composition and the nutritional status and the (digestibility of the diets of Sarotherodon mossambicus from nine reservoirs in Sri Lanka were evaluated. 'The feeding habits of S. mossambicus were variable from reservoir to reservoir; they ranged from herbivory to total carnivory. The protein, total lipid, carbohydrate and total organic matter content of the ingested material were related to the dietary composition and ranged from 18.53% to 35.15% (t-24.18%), 5.94% to 9.84% (X-7.91%), 11.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
1
26
1
1
Order By: Relevance
“…An alternative hypothesis is that algal carbon is being consumed not as deposited living algae, but rather as detritus formed from decomposition or excretion of the algae, and that could not be measured as chlorophyll. The organic matter ingested by L. pardalis and P. nigricans is within the broad ranges (5-70%) reported for other fish belonging to this trophic guild (Gneri & Angelescu, 1951;Bowen, 1979Bowen, , 1982Odum, 1973;Bowen et al, 1984;De Silva et al, 1984;Araujo-Lima & Hardy, 1987;Almeida et al, 1993;Sutton & Bowen, 1994;Yap, 1995;Resende et al, 1995;Catella, unpubl.). Crude protein contents were similar to the values reported for P. platensis and Tilapia mossambica (Peters) in South America (3·5-12%) (Bowen, 1981(Bowen, , 1984.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…An alternative hypothesis is that algal carbon is being consumed not as deposited living algae, but rather as detritus formed from decomposition or excretion of the algae, and that could not be measured as chlorophyll. The organic matter ingested by L. pardalis and P. nigricans is within the broad ranges (5-70%) reported for other fish belonging to this trophic guild (Gneri & Angelescu, 1951;Bowen, 1979Bowen, , 1982Odum, 1973;Bowen et al, 1984;De Silva et al, 1984;Araujo-Lima & Hardy, 1987;Almeida et al, 1993;Sutton & Bowen, 1994;Yap, 1995;Resende et al, 1995;Catella, unpubl.). Crude protein contents were similar to the values reported for P. platensis and Tilapia mossambica (Peters) in South America (3·5-12%) (Bowen, 1981(Bowen, , 1984.…”
Section: Discussionsupporting
confidence: 67%
“…The tracers used were HROM and hydrolysis-resistant ash (HRA), both of which are not affected by digestive processes (Buddington, 1980;Bowen, 1981Bowen, , 1984De Silva et al, 1984;Galetto & Bellwood, 1994). The calculations were done separately and the digestibility was estimated by standard calculations (Smith, 1989).…”
Section: Sample Processingmentioning
confidence: 99%
“…Other workers reported that A.E. values obtained using all the above three reference materials did not show significant differences (De Silva et al, 1984). Further, higher A.E.…”
Section: Discussionmentioning
confidence: 92%
“…This so-called detritivore is labeled as a notorious diet switcher (see Chapter 11), varying all the way from an algae-detritus diet to a carnivorous one (DeSilva et al, 1984;DeSilva, 1985). In fact Maitipe and DeSilva (1985) describe detritivorous, phytophagus, and zoophagus populations in 12 Sri Lankan reservoirs with seasonal variations occurring among the feeding types.…”
Section: Diet Switchingmentioning
confidence: 99%